Bantuan Hukum Bagi Masyarakat Dalam Meningkatkan Akses Keadilan Di Indonesia - Muhammad Arif Sahlepi (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
Legal aid constitutes the constitutional right of every citizen to the legal protection and equality guarantees before the law stipulated in Law Number 16 of 2011, as a means of recognition of human rights. So far the provision of legal aid we realize has not much touched the poor. Thus, the poor are still difficult to access justice. The problem in this research is how to give free legal aid to increase access of justice for society in Indonesia. Based on the results of research on the implementation of Legal Aid to the poor in North Sumatra, it can be concluded that the implementation of Legal Aid for the poor People in the province is not optimal yet since the aid cannot be felt by all levels of society, especially the poor in the province. Then, the poor still find difficulty to access and to obtain free legal aid so that it becomes homework for the government, the parties providing legal aid and Legal Aid Institute. Providing legal aid to the poor in North Sumatra should be given more attention. The improvements of regulations or legislation in particular that regulate the APBD (Regional Income Budget)  must be re-strengthened to realize equality before law. Keywords: Legal Aid, Justice, The Poor